From Brooke to Black Pastoral: Six Studies in Irish Literature and Culture. Litteraria Pragensia 10.20 (2000). 101 pp. - Csikai, Zsuzsa (FOCUS: Papers in English Literary and Cultural Studies, 2024)
The editors of this special issue of Litteraria Pragensia, the publication of the Faculty of Arts of Charles University, Prague, hope to illuminate certain issues of the current debate in Irish literary and cultural studies. They perceive that contemporary writing in and on Ireland demonstrates a strong intention of writers to advocate a “plurality of perspectives on the general cultural issues”, and to reflect this phenomenon in their publication the editors selected essays that are not unified in terms of either a specified theme or a critical approach.